Recovery of Bacillus cereus cyclodextrin glycosyltransferase using ionic liquid-based aqueous two-phase system - Ng, Hui Suan; Ooi, Chien Wei; Show, Pau Loke; Tan, Chin Ping; Ariff, Arbakariya; Mokhtar, Mohd Noriznan; Ng, Eng Poh; Ling, Tau Chuan (Pergamon Press, 2014)
Ionic liquids-based aqueous two-phase system (ILATPS) offers immediate phase separation and thus reduces the overall processing time, is significantly advantageous as compared to conventional ATPS such as polymer/polymer ATPS and polymer/salt ATPS. In this study, ILATPSs composed of imidazolium-based ionic liquid (IL) and salt were experimentally evaluated for their efficiencies in recovering Bacillus cereus cyclodextrin glycosyltransferase (CGTase) from fermentation broth. The phase-forming behavior of 1-ethyl-3-methylimidazolium tetrafluroborate, (Emim)BF4/sodium citrate ILATPS and (Emim)BF4/sodium carbonate ILATPS were first studied by constructing the binodal curves. Effects of the ILs concentration, pH value, feedstock loading, and addition of sodium chloride (NaCl) on the recovery of CGTase in ILATPS were investigated. The optimum conditions for the recovery of CGTase were obtained in an ILATPS consisting of 35% (w/w) (Emim)BF4, 18% (w/w) sodium carbonate and 3% (w/w) NaCl. Experimental results showed that 78% of CGTase could be recovered in the IL-rich phase in single-step purification with a purification fold (PF) of 15.4. The high PF indicates that this ILATPS is feasible to be applied in the recovery and separation of CGTase from the fermentation broth.